(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Infestation of Ephestia kiihniella in a food industry was controlled by using laminar and "rubber string" dispensers imbued with a high quantity of TDA. Trials lasted more than two years. The dispensers were placed on the walls and under the machineries in crevices with high infestation. The mating suppression can be obtained when a daily average distribution of 2.5 (±1) μg/m3 of TDA for at least 4 months has been mantained.